Анна Керн. Муза А. С. Пушкина - Фомина Лада (Женщины-легенды, 2021)
Экземпляры: аб. ЦБ (20240726) / Инвентарный номер: 23013 / Цена: / Сис.шифр: 83.3(2=Рус)1-8 / Авт.знак: Ф 76 / ГРНТИ: 17 / ББК: 83.3(2=Рус)1-8